Memory and Authenticity - Randolph Starn (Studies in 20th & 21st Century Literature, 1999)
Ten years ago Natalie Davis and I decided to put together a special issue of Representations we would call "Memory and Counter-Memory…
Keywords: Natalie Davis; Representations; memory; counter-memory; authenticity